Narrating the Self between Heterodoxy and Tradition. The Use of Personal Documents in Late Modernity - Toscano, Giuseppe (Italian Sociological Review, 2020)
Thomas and Znaniecki’s highly celebrated contribution to the methodology of social research is mainly due to the kind of data they used in their well-known work The Polish Peasant: an enormous number of personal documents. However, treating autobiographies and personal narratives as empirical data can raise objections not only because they are reconstructive experiences, but also due to the formal characteristics of the narrative reconstruction. A tale of one’s own life is, to all intents and purposes, a literary genre, which consists of a subjective selection of facts reported following rhetorical and stylistic conventions. Fiction narratives and reality narratives actually belong to the same continuum and this is quite clear from the recent trend in mixing different genres. Fictional tales are sometimes loosely based on real events. Surveys, inquiries, reports, diaries and pamphlets are often made up of a patchwork of reality and fiction. The boundaries between entertainment and information tend to disappear. In the light of this new scenario, what are the outcomes of the use of biographical documents in sociological research? Many symbolic interactionists have moved away from orthodoxy, proposed a radical use of biography and autobiographies, introduced new ways of reporting - even borrowing from the arts - and developed new techniques such as autoethnography. The aim of this paper is to analyze and discuss some recent trends in the use of personal documents, highlighting the various needs they can fulfill by improving and deepening hermeneutic approaches, and, on the other hand, the possible risks and drawbacks of the most radical choices and experimentations.